Diskresi Hakim Berbasis Kemaslahatan dalam Penetapan Nafkah Pascaperceraian: Studi Sosio-Legal Perkara Verstek di Pengadilan Agama Kota Kediri - Nur Kholisoh; Ahmad Badi' (JOM, 2026)
Post-divorce maintenance is a critical issue in Indonesian family law, particularly in verstek divorce cases where the absence of one party may affect the judicial determination of the wife’s post-divorce rights. This study aims to examine how judicial discretion is exercised in determining post-divorce maintenance in verstek proceedings, how the principle of maslahah informs judicial reasoning, and how social justice is reflected in decisions of the Kediri City Religious Court. Employing a normative-empirical juridical approach, the study analyzes Court Decision Number 475/Pdt.G/2024/PA.Kdr. and draws on interviews and documentary evidence to examine the relationship between legal norms and judicial practice. The findings indicate that the judge’s determination of post-divorce maintenance involved discretionary reasoning oriented toward protecting the wife’s rights and preventing potential harm arising from the divorce. This reasoning is reflected in the application of the fiqh maxim dar’u al-mafāsid muqaddamun ‘ala jalbi al-maṣāliḥ, which prioritizes the prevention of harm over the attainment of benefit. The case further illustrates that verstek proceedings do not necessarily preclude judicial consideration of the absent party’s legal interests, particularly where judicial discretion is directed toward substantive protection rather than merely procedural resolution. Theoretically, the study contributes to the discourse on Islamic family law by demonstrating how maslahah-based judicial discretion can mediate between formal procedural rules, the protection of women’s post-divorce rights, and the substantive realization of social justice in Religious Court adjudication.